Perencanaan DKM Al-Muhajir Bandung dalam Meningkatkan Pelayanan Jamaah - Aisyah, Kasi Ainun; Machendrawaty, Nanih; Sanusi, Irfan (Tadbir: Jurnal Manajemen Dakwah, 2021)
This study aims to determine the elements of planning, planning steps, as well as the advantages and disadvantages of planning at Masjid Al-Muhajir. This study uses a descriptive method with a qualitative approach. Data collection was carried out by means of observation, interviews, document study, and audio recordings. The results of this study indicate that there is an element of planning in which there are 5W + 1H. The planning steps include evaluation of previous activities, receiving some input from the congregation for the activities to be planned. For the benefit, activities become more focused and structured, activities run optimally, and are easy to evaluate. The disadvantages are that there are several activities that are not realized, as well as concerns about mosque budgets, because mosque finances are only racing on the infaq box.